PERAN SENTRAL MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN LEMBAGA PENDIDIKAN ISLAM - Qurroti A’yun (Vicratina : Jurnal Ilmiah Keagamaan, 2018)
One of the responsibilities of the principal as a manager is to improve the quality of human resources. Human resources management functions to organize school personnel in their expertise and social relations, ranging from hired personnel to their career development. Islamic educational institutions have very important role in the context of the spread of Islamic perspective. Human resources (humanware) and educational hardware have a very vital role to create a quality education and form smart, character, moral, and personable students.Keywords: management, human resources